Myth and the younger epic: problems of diffusion (based on the materials of legend and song about Lezherokopsh) - Lyana A. Gutova (Кавказология, 2023)
The article examines the patterns of use of mythological motifs in the cycle of the younger, historical-heroic epic. It is established by analyzing the song and legend about Prince Lezheroko (Lezherokopsh) that elements of mythological concepts have a subordinate place in the younger epic, but they can play a major part in the plot’s development. Their use is related to how stable the beliefs associated with existing beliefs are in the collective consciousness. Thus, we may not be talking about a consciously accepted artistic invention, but about ideas existing in traditional society. In the specific case of the cycle about Lezheroko, the fantastic characters genies and the hero’s participation in the conflict between them are recognized as a reality that has a direct connection with reality. The same is the nature of the use of elements of mysticism in some other cycles. This preserves the established generic feature of the younger epic - the perception of the events and personalities described as having a real factual basis in reality. This circumstance does not reduce the level of aesthetic significance of the elements of mythology in the lyrics of songs and legends of the younger epic, but introduces its diversity into the artistic system of the genre.